2009
DOI: 10.1038/sj.bjc.6605169
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric germ cell tumours and congenital abnormalities: a Children's Oncology Group study

Abstract: METHODS: Maternally reported congenital abnormalities (CAs) were examined in a case -control study of 278 cases of paediatric germ cell tumours (GCTs) and 423 controls. RESULTS AND CONCLUSIONS: Germ cell tumours were significantly associated with cryptorchidism in males (OR ¼ 10.8, 95% CI: 2.1 -55.1), but not with any other specific CA in either sex. The risk factors for paediatric germ cell tumours (GCTs), which comprise a histologically heterogeneous group of tumours affecting an estimated 360 individuals o1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 16 publications
3
23
1
Order By: Relevance
“…Evidence suggests that at least some risk factors, such as cryptorchidism 47, 48 , overlap for pediatric and adult testicular GCTs; however, the distinct clinical 3, 19, 49, 50 and genetic profiles 51-53 of pediatric and adult GCTs provide support for distinct etiologies. Several mechanisms have been hypothesized for the increase in testicular GCTs in males, with much attention focused on exposure to estrogens and environmental hormone disruptors 54 ; however, the exact mechanism is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that at least some risk factors, such as cryptorchidism 47, 48 , overlap for pediatric and adult testicular GCTs; however, the distinct clinical 3, 19, 49, 50 and genetic profiles 51-53 of pediatric and adult GCTs provide support for distinct etiologies. Several mechanisms have been hypothesized for the increase in testicular GCTs in males, with much attention focused on exposure to estrogens and environmental hormone disruptors 54 ; however, the exact mechanism is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…[2] There is no documented literature on any other association of gonadal or EGGCT with congenital abnormalities. The HSK is the most common type of renal fusion anomaly and can be related to teratogenic events affecting the urinary system (Wilms tumor and carcinoid tumors).…”
Section: Discussionmentioning
confidence: 99%
“…The HSK is the most common type of renal fusion anomaly and can be related to teratogenic events affecting the urinary system (Wilms tumor and carcinoid tumors). [2] Kidney is one of the least common locations for EGGCT teratomas, with only one case report of a child with HSK and intrarenal teratoma. [3]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Congenital abnormalities of the genital organs have been found to be associated with childhood GCT [5, 6, 8, 11] and studies have indicated increased risk of these abnormalities following intracytoplasmic sperm injection (ICSI) [14, 15]. Another study noted an increased risk of cryptorchidism after intrauterine insemination, although there was no increase after in vitro fertilization or ICSI [16].…”
Section: Introductionmentioning
confidence: 99%